ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK MIE GACOAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi pada Pelanggan Mahasiswa Universitas Bhayangkara Jakarta Raya) - Dhiandra Namira Invionita; Jenio Prawirodinata, Khilda Fadilatun Nissa, Najwa Fitri Alfiana Putri, Shellvia Cahya Ramadhani, Di (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to see how the quality and price of Mie Gacoan products influence consumers' decisions to buy what they want. The research results show that product quality has a positive and significant effect on consumers' decisions to buy what they want, while price has a negative and insignificant effect. The results of this research also show that product quality makes the biggest contribution to consumers' decisions to buy what they want, among other things. Thus, the Mie Gacoan company can improve the quality of its products so that customers prefer to buy their products.